Can soil phosphorus sorption saturation estimate future potential legacy phosphorus sources?. Issue 1 (3rd December 2020) - Sharpley, A. N.; Brye, K. R.; Burke, J. M.; Berry, L. G.; Daniels, M. B.; Webb, P.
Abstract: Various soil extraction methods are used to indicate plant available P in soil but do not account for soil specific sorption of subsequent applications of P. Thus, estimates of soil phosphorus sorption saturation (PSS; estimated from Mehlich‐3 extractable P, Al, and Fe) have been used in conjunction with Mehlich‐3 extractable soil phosphorus (M3P) to overcome these limitations. As less is known about the effect of land management on PSS than M3P under field conditions, the effect of field management on PSS was investigated for three pastures over 5 yr (2014–2018). Swine slurry was applied to two fields (Field 1 received 60 kg P and 74 kg N and Field 12 received 60 kg P and 74 kg N  ha −1  yr −1 ), mineral fertilizer to one field (Field 5 received 28 kg P and 64 kg N  ha −1  yr −1 ), and all fields grazed by cattle. Biannual grid‐soil sampling (0.1‐ha grid) showed an increase in PSS in the surface 10 cm of two fields receiving swine slurry (7.8–12.0% and 6.0–11.0% for Fields 1 and 12, respectively; P  < .05 level) between 2014 and 2018, while no change in PSS was evident for Field 5 receiving mineral fertilizer ( P  > .05 level). Compared with published values, measured increases in PSS suggest that soils of Fields 1 and 12 are transitioning from sinks to sources of P in specific areas of the field due to P applications and cattle grazing, and that management should change to minimize the potential for P runoff.